Analisis Kadar Senyawa Tanin Ekstrak Etanol Daun Pepaya Jepang (Cnidoscolus aconitifolius) Menggunakan Metode Spektrofotometri UV-VIS - Werdiningsih, Wiwik; Fitria, Faizatul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Japanese papaya plant (Cnidoscolus aconitifolius) can be used for traditional medicine such as antidiarrheal, antibacterial and antioxidant. The purpose of this study was to measure the levels of tannin compounds from the extraction of Japanese papaya leaves. This research method uses descriptive to measure the levels of tannin compounds in Japanese papaya leaf extract with UV-Vis spectrophotometry. Determination at Materia Medica Indonesia (MMI) to determine the maximum wavelength, determination of operating time, and determination of tannin content in the sample. The results showed that (1) quantitative test results with a maximum wavelength of 723 nm obtained an average tannin content of 36.782 mg TAE / g extract; (2) method validation test and the results met the requirements, namely the linearity test results obtained correlation coefficient (r2) s 0.9954; (3) accuracy test results of 98-102%; (4) precision test results RSD of 0.097%; (5) LOD and LOQ test results obtained 1.899 ppm and 5.755%.